Investigasi Terkait: Relevansi dan Validitas Rekaman sebagai Alat Pembuktian dalam Penanganan Tindak Pidana Korupsi di Indonesia - Nurhadi, Bayu (Universitas Ekasakti, 2023)
This research discusses the relevance and validity of recorded evidence as a means of proof in handling criminal acts of corruption in Indonesia. Through in-depth analysis, this research evaluates the role of recorded evidence in the judicial process, focusing on aspects of suitability, validity, and related challenges. Based on the results of the discussion, recorded evidence was proven to have significant relevance in enforcing corruption laws, providing clarity, transparency and reliability in revealing the facts that occurred. However, the validity of recorded evidence is highly dependent on its authenticity, reliability and compliance with applicable legal procedures. Challenges such as authentication, recording quality, and understanding legal rules are important factors that need to be overcome to ensure the effective and admissible use of recorded evidence in court. Therefore, this research concludes that the use of recorded evidence can strengthen corruption law enforcement in Indonesia, but careful steps are needed to ensure the validity and validity of this evidence.